The association between health literacy and e-cigarette use: evidence from Zhejiang, China - Zhang, Xuehai; Zhang, Xinxin; Zhang, Songjia; Ge, Lizheng; Xu, Yue; Yao, Dingning; Hu, Xiujing; Huang, Zishuo; Zhu, Tingting; Wang, Zixia; Chen, Chun (Frontiers in Public Health, 2024)
Objectives The worldwide popularity of electronic cigarettes (ECIG) is becoming a public health concern. Compared to conventional cigarettes (CIG), the harm caused by ECIG is more insidious. Studies have shown that lower health literacy (HL) is associated with CIG use; however, the relationship between HL and ECIG use remains controversial. Because ECIG emerged more recently than CIG, there are fewer relevant studies, and the sample populations and evaluation methods of HL in existing studies differ. This study conducted a large-sample survey to examine the relationship between HL and ECIG use. Methods As part of the 2022 China Health Literacy Survey, a total of 60,998 valid questionnaires were collected from September to November in 2022 using a stratified multistage probability proportional to the population size sampling frame. Chi-square tests and multinomial logistic regression was used to analyze the relationship between HL and ECIG use. Some demographic variables were included as covariates in the analysis. Results The study showed that the average HL score and the HL level of Zhejiang residents in 2022 were 42.8 and 30.8%, respectively. The prevalence of CIG and ECIG was 19.7 and 1.0%, respectively; 19% of participants exclusively used CIG, while only 0.3% of participants used ECIG exclusively; dual users accounted for 0.6%. After adjusting for covariates, adequate HL was associated with lower odds of ECIG-exclusive use (odds ratio [OR] = 0.452, p < 0.001), CIG-exclusive use (OR = 0.833, p < 0.001), and dual use (OR = 0.632, p < 0.001). Young age, male sex, unmarried status, high-income status, and absence of chronic disease were also associated with ECIG use. Conclusion HL was a protective factor against both patterns of ECIG use, especially ECIG-exclusive use. Health policymakers and public health practitioners should consider HL as a potential measure for ECIG control.